Causes of failure in SMEs - Popescu, Delia (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The author outlines main reasons for maladjustment of small and medium enterprises to market conditions. The causes may be divided into several groups: related to commercial offer management, company’s strategy management, use of human resources in management and entrepreneurial initiative. In various conditions these factors variously influence success or failure of small and medium enterprises.
Keywords: małe i średnie przedsiębiorstwa; zarządzanie przedsiębiorstwem; przedsiębiorczość